2020
DOI: 10.1038/s41396-020-00803-y
|View full text |Cite
|
Sign up to set email alerts
|

Life-history strategies of soil microbial communities in an arid ecosystem

Abstract: The overwhelming taxonomic diversity and metabolic complexity of microorganisms can be simplified by a life-history classification; copiotrophs grow faster and rely on resource availability, whereas oligotrophs efficiently exploit resource at the expense of growth rate. Here, we hypothesize that community-level traits inferred from metagenomic data can distinguish copiotrophic and oligotrophic microbial communities. Moreover, we hypothesize that oligotrophic microbial communities harbor more unannotated genes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(72 citation statements)
references
References 63 publications
3
68
0
1
Order By: Relevance
“…Overall, the metagenomic analysis displayed more functional redundancy and overall similarity between the various soils than perhaps was expected at the outset. It has recently been shown that arid ecosystem metagenomes appear to have higher proportions of genes that are unknown in reference databases ( 51 ), potentially leading to difficulties in annotating and, therefore, discriminating arid soil samples from temperate soil samples. However, the extracted taxonomic identities of the reads, and the specific functions encoded by them, in our quarry soils were more than sufficient to discriminate the various treatments and showed significant impacts of the restorations on community profiles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the metagenomic analysis displayed more functional redundancy and overall similarity between the various soils than perhaps was expected at the outset. It has recently been shown that arid ecosystem metagenomes appear to have higher proportions of genes that are unknown in reference databases ( 51 ), potentially leading to difficulties in annotating and, therefore, discriminating arid soil samples from temperate soil samples. However, the extracted taxonomic identities of the reads, and the specific functions encoded by them, in our quarry soils were more than sufficient to discriminate the various treatments and showed significant impacts of the restorations on community profiles.…”
Section: Discussionmentioning
confidence: 99%
“…In general, soil microbial diversity has been mainly studied using 16S rRNA gene analyses (here referred to as 16S) until most recently ( 38 40 ), but this method provides only taxonomic information. However, in the last decade, the application of culture-independent (meta)genomics approaches ( 37 , 41 ) based on high-throughput DNA sequencing has proved a promising tool to investigate the abundance of specific genes, entire functional profiles, and ecological significances of microbial communities living in diverse ecosystems ( 3 , 42 51 ). As metagenomic analysis forgoes using selective primers and PCR, it is widely considered a much less biased approach to analyze communities—although challenges still remain in having adequate database coverage of novel organisms, the preponderance of unknown functions, and the fact that gene presence does not necessarily equate to expressed function ( 52 , 53 ).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, may a high frequency of GC pairs that have three hydrogen bounds compared to only two hydrogen bounds in AT pairs enhance the resistance of cells with high GC content against some specific stressors, such as heat or desiccation stress. Probably for this reason, a higher GC content was found in arid, nutrient-poor soils exposed to heat and dehydration stress than in soils with higher nutrient contents but lower stress exposure (Chen et al, 2020). Lauro et al (2009) suggested that high RRN, an elevated number of prophages and a large genome size are more common in marine copiotrophic than in marine oligotrophic bacteria.…”
Section: Genomic Traits As Life History Proxies In Prokaryotesmentioning
confidence: 99%
“…Lauro et al (2009) suggested that high RRN, an elevated number of prophages and a large genome size are more common in marine copiotrophic than in marine oligotrophic bacteria. In contrast, nutrient additions to soil environments resulted in the selection of prokaryotes with smaller genomes (Leff et al, 2015) and a recent comparison of microbial communities in nutrient rich versus nutrient depleted soils did not reveal a significant difference in their average genome sizes (Chen et al, 2020). In addition, enhanced CUBs were found associated with copiotrophic microbial communities in soil environments (Chen et al, 2020).…”
Section: Genomic Traits As Life History Proxies In Prokaryotesmentioning
confidence: 99%
“…The balance between r -selection and K -selection strategies in a community determines the productivity levels of communities and the survival of individuals (Pianka, 1970;Reznick et al, 2002;Ye et al, 2018). In addition, soil microorganisms in arid ecosystems tend to host oligotrophic communities rather than copiotrophic communities, highlighting the potential of oligotrophic microbial communities to serve as rich sources of novel functions under resource scarcity (Chen et al, 2021). In contrast, the accumulation of soil nutrients such as N promotes a more active copiotrophic community as a result of the shift in microbial phylogenetic, metagenomic and catabolic responses (Fierer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%